Location and Histological Pattern of Lung Carcinoma in Relation to the Smoking Habit - Hasan, Mohammad Towfique; Uddin, Jalal Mohsin; Yasmin, Mahfuza Tayeba; Chatterjee, Mohua; Roy, Chandon (Sir Salimullah Medical College Journal, 2025)
Background: Lung cancer is the leading cause of cancer-related mortality worldwide, with smoking as the principal risk factor. The histological subtypes of lung cancer, including adenocarcinoma, squamous cell carcinoma, and small cell carcinoma, vary according to smoking history and intensity. This study investigates the effect of smoking duration on the histological subtypes of lung cancer in Bangladesh. Methods: A cross-sectional study was conducted at the National Institute of Diseases of the Chest and Hospital (NIDCH) from July 2021 to June 2022. A total of 81 patients with confirmed primary lung cancer were included who were smokers. Results: Among the 81 patients, 37%% had adenocarcinoma, 33.3% squamous cell carcinoma, 19.8% small cell carcinoma, 6.2% large cell carcinoma, and 3.7% other subtypes. Smokers exhibited a higher incidence of adenocarcinoma. Majority (79.01%) of the patients with lesions in the upper lobe was smokers compared to 20.99%% of patients with lesions in the lower lobe (p < 0.001). Ratio of upper and lower lobe tumour among smoker was roughly of 4:1.A significant association was found between smoking duration and the occurrence adenocarcinoma.Conclusion: In our research releveled that smoking duration has a significant impact on the histological types oflung carcinomas especiallyadenocarcinomas are more prevalent in smokerswhich affect the upper lobe predominantly. Sir Salimullah Med Coll J 2024; 32: 10-15